A preliminary assessment of the effect of PreCR™ DNA repair treatment on mixture ratios in two person mixtures. Issue 5 (September 2018) - San Pietro, David; Tagliaro, Franco; Adamowicz, Michael S.
Abstract: In this study, DNA extracted from known buccal samples was combined into two component mixture samples. These were subjected to UV exposure prior to their amplification with the Promega PowerPlex® 16HS amplification kit, and subsequent capillary electrophoresis on the ABI 3130xl instrument. Damaged samples were subjected to enzymatic repair treatment and retested to assess the amount of repair. Data showed that there is fidelity associated with the application with profile concordance after its use, and a corresponding increase in the amount of recovered alleles post damage. Results also showed changes in the stochastic relationship between mixture components that appear to be induced by the repair process itself. The mixture ratios of DNA samples were altered from an approximate original 1:3 ratio, to a ratio of 1:2 or greater. This variation can have a significant effect regarding the ability to reliably de-convolute DNA mixtures that have been subjected to the repair process. Highlights: The PreCR™ DNA repair reagent was assessed for use with two person mixtures. Stochastic effects were evaluated on resulting Mixture Proportions (MP). MP variations were evaluated for possible effect on deconvolution status. At 1:1 and 1:3 ratios, calculated MP's shifted, effecting deconvolution conditions. Possible reasons for this are discussed.